An alcohol-free beer enriched with isomaltulose and a resistant dextrin modulates gut microbiome in subjects with type 2 diabetes mellitus and overweight or obesity: a pilot study. Issue 8 (31st March 2021) - Mateo-Gallego, Rocío; Moreno-Indias, Isabel; Bea, Ana M.; Sánchez-Alcoholado, Lidia; Fumanal, Antonio J.; Quesada-Molina, Mar; Prieto-Martín, Ascensión; Gutiérrez-Repiso, Carolina; Civeira, Fernando; Tinahones, Francisco J.
Abstract : An alcohol-free beer including the substitution of regular carbohydrates for low doses of isomaltulose and maltodextrin within meals significantly impacts gut microbiota in diabetic subjects with overweight or obesity. Abstract : We aimed to study the effect of consuming an alcohol-free beer with modified carbohydrates composition (almost completely eliminating maltose and adding isomaltulose (16.5 g day −1 ) and resistant maltodextrin (5.28 g day −1 )) in gut microbiome, compared to regular alcohol-free beer in subjects with T2DM or prediabetes and overweight/obesity. This is a pilot, randomized, double-blinded, crossover study including a sub-sample of a global study with 14 subjects: (a) consuming 66 cl day −1 of regular alcohol-free beer for the first 10 weeks and 66 cl day −1 of modified alcohol-free beer for the next 10 weeks; (b) the same described intervention in opposite order. BMI homogeneously decreased after both interventions. Glucose and HOMA-IR significantly decreased just after the participants consumed modified alcohol-free beer. These findings were in the same line as those reported in the global study. Dominant bacteria at baseline were Bacteroidetes, Firmicutes, Proteobacteria and Tenericutes . Parabacteroides, from the Porphymonadaceae family, resulted as the feature with the greatest difference between beers (ANCOM analysis, W = 15). Feature-volatility analysis confirmed the importance of Parabacteroides within the model. Alcohol-free beers consumption resulted in an enhancement of pathways related to metabolism according to PICRUSt analysis, including terpenoid-quinone, lipopolysaccharides and N -glycan biosynthesis. Thus, an alcohol-free beer including the substitution of regular carbohydrates for low doses of isomaltulose and the addition of maltodextrin within meals significantly impacts gut microbiota in diabetic subjects with overweight or obesity. This could, at least partially, explain the improvement in insulin resistance previously found after taking modified alcohol-free alcohol. Clinical Trial Registration: Registered under ClinicalTrials.gov identifier no. NCT03337828.